Experimental Study of Bond Behavior Between Rebar and PVA-Engineered Cementitious Composite (ECC) Using Pull-Out Tests - Xiao, Jie; Long, Xiang; Ye, Ming; Jiang, Haibo; Liu, Lingfei; Zhai, Keyi (Frontiers in Materials, 2021)
As a novel civil engineering material, Engineered Cementitious Composite (ECC) has attracted more and more attention due to its strain-hardening characteristics, good post-cracking resistance and its unique properties. Bonding between Engineered Cementitious Composite (ECC) and rebar has a great effect on the mechanical behavior of structural members. In this paper, direct pull-out tests were conducted to understand the bond behavior between the ECC and rebar. The test parameters included rebar diameter and type, cover layer thickness, embedment length and fiber volume content. Bond-slip curves, failure and cracking pattern and bond strength were compared and discussed. The test results indicated that the bond strength decreased with the increase of embedded length. Through regression analysis with the test data, the functional relationships between bond strength and cover layer thickness and rebar diameter were fitted well. According to the positive and negative signs of the fitting parameters m and n, the relationship between the bond strength and the cover layer thickness and the rebar diameter could be determined. The bond strength increased obviously with the increase of fiber content. When the fiber volume content was 1%, 1.5% and 2%, the bond strength of these specimens were 1.5, 2.5 and 3.1 times that of specimens without polyvinyl alcohol (PVA) fiber.